2013
DOI: 10.1164/rccm.201207-1294oc
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Generated at Mitochondrial Complex III Triggers Acute Responses to Hypoxia in the Pulmonary Circulation

Abstract: Rationale: The role of reactive oxygen species (ROS) signaling in the O 2 sensing mechanism underlying acute hypoxic pulmonary vasoconstriction (HPV) has been controversial. Although mitochondria are important sources of ROS, studies using chemical inhibitors have yielded conflicting results, whereas cellular models using genetic suppression have precluded in vivo confirmation. Hence, genetic animal models are required to test mechanistic hypotheses. Objectives: We tested whether mitochondrial Complex III is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
149
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 47 publications
7
149
1
1
Order By: Relevance
“…The acute pulmonary vasoconstriction response was then compared in the knockout and control mice, by measuring the right ventricular systolic pressure (RVSP) response to acute alveolar hypoxia. Control mice exhibited a significant increase in RVSP during 5% O 2 ventilation, which was significantly attenuated in the RISP-deficient mice (93). These findings indicate that a functional complex III is required for the acute vasopressor response to hypoxia in the lung.…”
Section: Mitochondrial Oxygen Sensingmentioning
confidence: 70%
See 2 more Smart Citations
“…The acute pulmonary vasoconstriction response was then compared in the knockout and control mice, by measuring the right ventricular systolic pressure (RVSP) response to acute alveolar hypoxia. Control mice exhibited a significant increase in RVSP during 5% O 2 ventilation, which was significantly attenuated in the RISP-deficient mice (93). These findings indicate that a functional complex III is required for the acute vasopressor response to hypoxia in the lung.…”
Section: Mitochondrial Oxygen Sensingmentioning
confidence: 70%
“…After loss of RISP was confirmed, subsequent roGFP studies demonstrated that the hypoxia-induced changes in redox status in the cytosol, IMS, and the mitochondrial matrix were abolished. These studies therefore demonstrated that a functional complex III was required for the changes in redox observed in different subcellular compartments during hypoxia (93). In parallel studies, it was found that the transient increase in cytosolic Ca 2ϩ in PASMC during acute hypoxia was abrogated in cells where RISP had been deleted (93).…”
Section: Mitochondrial Oxygen Sensingmentioning
confidence: 94%
See 1 more Smart Citation
“…While there has been considerable advancement in the development of mitochondria-targeted small molecule antioxidants (3) and alternative approaches to targeting mROS (133)(134)(135)(136)(137) appear promising, such mROS-targeted therapeutic approaches must be used with caution. mROS behave as a cytoprotective agent that leaves cells less susceptible to sub- …”
Section: Therapeutic Targeting Of Mitochondria In Lung Diseasementioning
confidence: 99%
“…The elevated NAPE-PLD protein expression in PASMCs under hypoxia can explain enhanced AEA levels, even though a contribution of other recently identified enzymes capable of AEA generation such as α/β-hydrolase 4 (Abh4) and glycerophosphodiesterse 1 (GDE1) (27) or protein tyrosine phosphatase, nonreceptor type 22 (PTPn22) (28), cannot be excluded. Moreover, there are recent indications that reactive oxygen species (ROS) are involved in the modulation of pulmonary vascular tone by hypoxia (29). Because AEA has been reported to lead to ROS formation (30), a link between these two pathways also appears possible.…”
Section: Discussionmentioning
confidence: 99%